Proof without words: beyond the parallelogram law - Alsina, C.; Monreal, A. (Teaching Mathematics and Computer Science, 2003)
We present a visual proof of the parallelogram law and using it we can describe a visual proof of a classical theorem on convex quadrilaterals relating sides and diagonals.